The prostitute's allure: Examining returns to beauty, productivity and discrimination - Raj Arunachalam; Manisha Shah (Institute for the Study of Labor (IZA), 2010)
We estimate the earnings premium for beauty in an occupation where returns to physical attractiveness are likely to be important: commercial sex work. In the commercial sex market, perhaps more so than any other sector in the labor market, the beauty premium should be at the extreme due to the intimate interpersonal relationships required with clients. Therefore, the commercial sex sector provides the cleanest test for whether the beauty premium is driven solely by productivity. Somewhat surprisingly we find estimates that lie close to or comfortably within those for non-sex workers around the world. In fact, the estimated premium for above average beauty is only slightly larger than that estimated for women elsewhere, and the penalty for below average looks lies comfortably within the range of existing findings. We show that the beauty premium in the commercial sex market stems both from productivity and discrimination. In addition, including controls for personal characteristics (communication ability and desirability of personality) cuts the beauty premium by up to one-half. Our findings suggest that beauty premiums might be overestimated if measures akin to those in our dataset are not included in beauty regressions.
Keywords: J01; J71; 330; beauty premium; discrimination; sex markets; Prostitution; Frauen; Sexualität; Wahrnehmung; Diskriminierung; Rendite; Schätzung; Mexiko; Ecuador